Renal K+ retention in physiological circumstances: focus on adaptation of the distal nephron and cross-talk with Na+ transport systems - Lasaad, Samia; Crambert, Gilles (Frontiers in Physiology, 2023)
Consumption of salt (NaCl) and potassium (K+) has been completely modified, switching from a rich-K+/low-NaCl diet in the hunter–gatherer population to the opposite in the modern, westernized population. The ability to conserve K+ is crucial to maintain the plasma K+ concentration in a physiological range when dietary K+ intake is decreased. Moreover, a chronic reduction in the K+ intake is correlated with an increased blood pressure, an effect worsened by a high-Na+ diet. The renal adaptation to a low-K+ diet in order to maintain the plasma K+ level in the normal range is complex and interconnected with the mechanisms of the Na+ balance. In this short review, we will recapitulate the general mechanisms allowing the plasma K+ value to remain in the normal range, when there is a necessity to retain K+ (response to low-K+ diet and adaptation to gestation), by focusing on the processes occurring in the most distal part of the nephron. We will particularly outline the mechanisms of K+ reabsorption and discuss the consequences of its absence on the Na+ transport systems and the regulation of the extracellular compartment volume and blood pressure.